(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Ecuador’s constitution protects non-human animals in two ways: through explicit provisions and through a broad interpretation of Article 71 on the rights of nature. This paper focuses on the implications of the recognition of animal rights through Article 71 of the Constitution and aims to answer three questions: Does the individual protection extend to all species or only to certain categories? What rights are granted to animals? Are there limits to the exercise of these rights?